Behavioral Biometric Data Analysis for Gender Classification Using Feature Fusion and Machine Learning - Gornale, Shivanand S.; Kumar, Sathish; Patil, Abhijit; Hiremath, Prakash S. (Frontiers in Robotics and AI, 2021)
Biometric security applications have been employed for providing a higher security in several access control systems during the past few years. The handwritten signature is the most widely accepted behavioral biometric trait for authenticating the documents like letters, contracts, wills, MOU’s, etc. for validation in day to day life. In this paper, a novel algorithm to detect gender of individuals based on the image of their handwritten signatures is proposed. The proposed work is based on the fusion of textural and statistical features extracted from the signature images. The LBP and HOG features represent the texture. The writer's gender classification is carried out using machine learning techniques. The proposed technique is evaluated on own dataset of 4790 signatures and realized an encouraging accuracy of 96.17%, 98.72% and 100% for k-NN, decision tree and Support Vector Machine classifiers, respectively. The proposed method is expected to be useful in design of efficient computer vision tools for authentication and forensic investigation of documents with handwritten signatures.